Healing of an immature permanent tooth with large periapical radiolucency, treated with autologous platelet-rich fibrin aided regeneration - Preet Kanwal Atwal; Gauri Malik; Shivani Khanna (Wolters Kluwer Medknow Publications, 2024)
Presenting two cases of platelet-rich fibrin (PRF) aided regenerative treatment, performed in immature permanent teeth with large periapical lesions. In contrast to conventional apexification procedures, regenerative procedures can promote root completion and achieve root reinforcement. These case reports evaluated the long-term biological outcome of PRF-aided regeneration in immature permanent teeth with periapical lesions. Three-year and 5-year recalls in these cases revealed functional teeth with complete healing of the large periapical defect. The secondary outcome of regenerative treatment varied in the two reported cases. It was concluded that enhanced repair was achieved by an autologous PRF-aided regenerative procedure, but the secondary outcomes manifest variation.